Pengaruh Holding Time Terhadap Kekerasan Material Bilah Gangsa Gamelan Bali - Paskah Aprian Damanik, Simon; Priambadi, I Gusti Ngurah; Nata Septiadi, Wayan (Teknik Desain Mekanika, 2021)
Abstract The choice of musical material must take into account the mechanical and acoustic properties of the material. The material commonly used for gamelan is tin bronze, so this study used an alloy of 80% Cu - 22% Sn. Specimen making is done by means of material preparation, smelting process, pouring process, cooling process and casting process. To determine the effect of holding time on the mechanical properties of material hardness, the Vickers hardness test method was used. The test results show that the holding time temperature treatment affects the mechanical properties of the alloy specimens. The highest yield was at the midpoint of the specimen with a distance of 1.5 m with a value of 37,343 VHN. The longer the specimen experiences a holding time and the temperature increases, the less its hardness value will be. Keywords: Balinese gamelan, holding time, tin bronze, vickers hardness